2017
DOI: 10.1111/cea.12954
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to oral prednisolone in severe asthma is related to the degree of eosinophilic airway inflammation

Abstract: SummaryBackground: Patients with severe asthma appear relatively corticosteroid resistant.Corticosteroid responsiveness is closely related to the degree of eosinophilic airway inflammation. The extent to which eosinophilic airway inflammation in severe asthma responds to treatment with systemic corticosteroids is not clear.Objective: To relate the physiological and inflammatory response to systemic corticosteroids in asthma to disease severity and the baseline extent of eosinophilic inflammation. Methods:Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 25 publications
2
28
1
Order By: Relevance
“…17 Following a two-week course of oral prednisolone, both groups experienced a similar degree of suppression of blood and airway eosinophilia and serum cytokines. Sousa and colleagues have explored this amongst a group of moderate and severe asthmatics.…”
Section: Asthma Clinical Managementmentioning
confidence: 95%
See 1 more Smart Citation
“…17 Following a two-week course of oral prednisolone, both groups experienced a similar degree of suppression of blood and airway eosinophilia and serum cytokines. Sousa and colleagues have explored this amongst a group of moderate and severe asthmatics.…”
Section: Asthma Clinical Managementmentioning
confidence: 95%
“…Sousa and colleagues have explored this amongst a group of moderate and severe asthmatics. 17 Following a two-week course of oral prednisolone, both groups experienced a similar degree of suppression of blood and airway eosinophilia and serum cytokines. Even in patients on high doses of inhaled steroids, many showed a suppressive eosinophil response.…”
Section: Asthma Clinical Managementmentioning
confidence: 95%
“…Prednisolone, one of the glucocorticoids, acts as endogenous cortisol that is released from the hypothalamic-pituitary-adrenal (HPA) axis, particularly in the case of stress or injury [9]. Prednisolone fights inflammation via the regulation of tumor necrosis factor-α (TNF-α), interleukin-1 (IL-1), and interleukin-6 (IL-6) etc, thus, widely applied to treating various inflammation diseases or states, such as allergies, asthma, dermatitis, rheumatic disorders, systemic lupus erythematosus, and autoimmune disorders [10][11][12]. Recently, Baudoux et al demonstrated that cluster of differentiation CD4 + and CD8 + T-cells regulate immune responses in AA-induced acute tubular necrosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Predictors of successful reduction were younger age and low blood eosinophils. There are interesting parallels with predictors of response to oral corticosteroids …”
mentioning
confidence: 99%